PRACTICAL ANALYSIS OF VIRTUAL BANKING IN THE IOT PROCESS IN THE DIGITAL ECONOMY ERA - Abduraхmonov Adxamjon Sultonboyevich (Ethiopian International Journal of Multidisciplinary Research, 2026)
Modern banks are providing appropriate contextualized service and advice enriching the interaction between clients. Biometrics – voice or touch – can simplify account access in these new “anywhere” digital channels. This will eliminate barriers associated with in-person, paper-based transactions and enable clients to conduct business even when they cannot be physically available in bank.